SOSIALISASI PENANGGULANGAN BULLYING BERBASIS TEAM BUILDING MENGGUNAKAN PSIKOEDUKASI DI SMK BINA SRIWIJAYA INDONESIA PALEMBANG - Sulastri, Asiawatie; Wahidin, Edison; Triana, Dora Indah (PT. Jurnal Center Indonesia Publisher, 2024)
Bullying cases in Indonesia occupy the top ranking. Bullying behavior often occurs when someone has shortcomings, both physically and mentally. The impact of bullying on students is in the form of decreased appetite, headaches, embarrassment, and feeling afraid to socialize in social environments. Increasing students' understanding regarding bullying behavior can reduce bullying cases. Bullying can start from uncontrolled levels of aggressive behavior during childhood. However, this can be prevented by increasing supervision of negative associations from children and friends, starting from modeling good things, filtering out children's friends who have a positive effect. The aim of this intervention is to provide students with understanding and knowledge regarding bullying, its types, etc. Bullying affects both boys and girls. The method based on this intervention consists of 4 stages, namely needs assessment for the Counseling Guidance teacher, distribution of bullying questionnaires to students, Focus Group Discussion (FGD) with students, provision of materials and games in team building. The series of activities were attended by 40 students consisting of 20 men and 20 women from several representatives of departments at Bina Sriwijaya Indonesia Palembang Vocational School. The results of the intervention activities that have been implemented are that students feel openness in terms of both thoughts and feelings regarding bullying behavior. The service activities at Bina Sriwijaya Indonesia Palembang Vocational School have had a very good impact on the entire school community, especially students, subject teachers, guidance and counseling teachers and all staff and equipment at the school. The Principal welcomed and looked forward to further positive activities at Bina Sriwijaya Indonesia Palembang Vocational School. From the results of a questionnaire conducted on community service participants, 87.5% of students strongly agreed with socialization activities to overcome bullying and 12.5% ​​agreed.